Positive solutions of critical quasilinear elliptic problems in general domains - Filippo Gazzola (Abstract and Applied Analysis)
We consider a certain class of quasilinear elliptic equations with a term in the critical growth range. We prove the existence of positive solutions in bounded and unbounded domains. The proofs involve several generalizations of standard variational arguments.